Spermatozoa Facts and Perspectives - Meccariello, Rosaria; Chianese, Rosanna (IntechOpen, 2018)
Spermatozoa, the haploid male gametes, are highly specialized cells capable to fertilize eggs in order to produce diploid zygote. The biogenesis of spermatozoa requires finely modulated occurrence of mitotic, meiotic, and differentiation events. Hence, the production of high-quality spermatozoa impacts fertilization with outcomes on the health of the offspring. This book provides a comprehensive overview on the biogenesis, maturation, functions and activities of spermatozoa in both physiological conditions and infertility. Particular attention has been addressed to the impact of environment on sperm quality and to the appropriate selection of high-quality spermatozoa for in vitro fertilization. Taken together, this book targets a wide audience of basic and clinical scientists, teachers and students, and offers a better understanding of spermatozoa health and disease.